(untitled) (Research, Society and Development, 2020)
Environmental education is as an alternative to raise awareness of sustainable agricultural practices, aiming to incorporate new practices in sustainability, capable of reducing or eliminating damage to the environment. In this sense, the socio-environmental reality of rural settlement projects can be favored with actions in favor of the socio-environmental and economic sustainability of these territories. In this article, the objective was to highlight the role of environmental education, as an inducing tool in encouraging environmental conservation practices, avoiding and / or mitigating the damage caused by inefficient land use in sustainable development projects (PDS’s) in Brazil. Methodologically, it consists of a qualitative research of bibliographic nature. It was possible to infer that Environmental Education consists of an important tool capable of sharing information, promoting social development and the training of settlers, based on paradigm breaks, encouraging sustainable use, and developing continuous processes of coexistence and respect for the environment.